PENERJEMAHAN, INTERTEKSTUALITAS, HERMENEUTIKA DAN ESTETIKA RESEPSI - Kuswarini, Prasuri (JURNAL ILMU BUDAYA, 2016)
AbstractTranslation is essentially an activity of reproducing equivalent signs in terms of language, culture, and themessage and its effect. Seen from from the main elements in translation, which are a messenger or awriter, a message or a text, a translator, and the recipient, then the activity of translation requires anapproach that can reach out to those four elements. This article is an overview of the approaches that canbe done to produce a good translation. The proposed approaches are intertextual studies, hermeneuticsand reception aesthetics. Translating with these three approaches not only pay attention to the relationshipbetween the existing code in the text, but also the relationship between the messenger or the author, andthe recipient or reader, with the involvement of the context that surrounds the author of the sourcelanguage and target language readers. In addition, the translator as a mediator is also taken into accountby promoting empathy with the author, and by maintaining at the same time the identity of the translator,who plays the role as reader of the target language as well.Key words : translation , intertextuality , hermeneutics , reception aesthetics , context , identity